Determinants of historical museums quality at Sharjah for museums digitization practices During the spread of covid -19: E-Visitor’s perceptions - Aburumman, Asad H.; Al-Leheabi, Saleh Muhammad Zeki (Al-Adab Journal, 2022)
The study of museums is one of the most important qualitative studies dealt with by many researchers in societies, the study aimed to measure the services quality of virtual museum from the viewpoint of visitors to museums and the impact on visitor’s satisfaction, the study used a set of dimensions to measure the quality of museums by default: website, interaction, reliability, privacy, safety, effectiveness, empathy, response. The study used a questionnaire, which was distributed to (375) visitors, the study concluded that the quality of museum services affects visitor satisfaction, and study showed the importance of visitors' trust in museum technology, and its role in encouraging visitors to visit the virtual